The Use of Sludge from Cow Manure Biodigester as Fertilizer and Carrier of Cordyceps sp. for White Grub Pest Control - Pertiwiningrum, Ambar (David Publisher, 2016)
Processing cow manure into biogas is a solution to reduce air pollutant, because it reduces the smell of the manure up to 70%. Besides producing biogas, the sludge of biodigester can also serve as solid and liquid fertilizer. The solid fertilizer can be used as carrier of entomopathogenic fungi to control the pest which lives underground. The research aimed to investigate the benefits of biodigester sludge as fertilizer and carrier of entomopathogenic fungi (Cordyceps sp.) to control white grub pest. The use of organic fertilizer and pesticide in the cultivation can minimize the environmental hazard. The method used in the study was completely randomized design with four treatments, which were the addition of Cordyceps sp. corn media as much as 0, 10, 20 and 30 g/kg of sludge. Every addition was repeated three times to corn planted in a tub. To examine the effect of the treatments, the data were analyzed with ANOVA and Duncan test was applied when differences occurred between treatments. The results of the research showed that the nutrients contained in the manure which had been processed into biogas were not lost. The plants cultivated in the planting medium supplemented with sludge grew healthier, bigger, taller and had stronger and longer roots. On the contrary, the plants cultivated without sludge addition were vulnerable to white grub attack. The Cordyceps sp., which was added into the sludge, was effective to control the white grub. The concentration of Cordyceps sp. as much as 20 g/kg of sludge in corn planting medium was the most effective concentration to control white grub pest.